2013
DOI: 10.1002/pro.2384
|View full text |Cite
|
Sign up to set email alerts
|

Development of a steady‐state FRET‐based assay to identify inhibitors of the Keap1‐Nrf2 protein–protein interaction

Abstract: One of the strategies proposed for the chemoprevention of degenerative diseases and cancer involves upregulation of antioxidant and free radical detoxification gene products by increasing the intracellular concentration of the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2). This can be achieved by disrupting the interaction between Nrf2 and Kelch-like ECH associated protein 1 (Keap1), a substrate adaptor protein for a Cul3-dependent E3 ubiquitin ligase complex. Here, we describe the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…For this purpose, ECFP was fused to the N terminus of STAT1ND or STAT1(1-713), while EYFP was fused to the N terminus of Y3. If ECFP is close to EYFP (within about 100 Å), emission from ECFP at 475 nm, which is generated after excitation of the ECFP chromophore at 435 nm, is decreased, while emission from EYFP at 527 nm is increased (32). Gel filtration analysis showed that ECFP-fused STAT1ND could bind to EYFP-fused Y3 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…For this purpose, ECFP was fused to the N terminus of STAT1ND or STAT1(1-713), while EYFP was fused to the N terminus of Y3. If ECFP is close to EYFP (within about 100 Å), emission from ECFP at 475 nm, which is generated after excitation of the ECFP chromophore at 435 nm, is decreased, while emission from EYFP at 527 nm is increased (32). Gel filtration analysis showed that ECFP-fused STAT1ND could bind to EYFP-fused Y3 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Numerous cell‐based and in silico screens have identified Nrf2‐activating compounds (Schaap, Hancock, Wilderspin, & Wells, 2013; Wang et al, 2013; Williamson et al, 2012; Wu, McDonald, Liu, Chaguturu, & Klaassen, 2012), including triterpenoid 2‐cyano‐3,12‐dioxooleana‐1,9(11)‐dien‐28‐oate‐methylamide (CDDO‐MA), puerarin, sulforaphane, CDDO‐ethyl amide and others. Nrf2 activators demonstrated activity in in vitro and in vivo in different neurodegenerative mouse models, protecting neurons, decreasing the accumulation of aberrant proteins and increasing life span (Buendia et al, 2016; Joshi and Johnson 2012).…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…Additionally, L75, L84 and D77 have been suggested to stabilise the beta‐turn structure. The binding of isolated, unconstrained peptides based on the ETGE motif of Nrf2 to Keap1 is well‐characterized through biophysical, crystallographic and cell‐based assays . Inhibiting this interaction has therapeutic potential for a range of diseases, such as the chemoprevention of cancer, diabetes Alzheimer's disease, and chronic obstructive pulmonary disease …”
Section: Introductionmentioning
confidence: 99%